2011
DOI: 10.1074/jbc.m111.233742
|View full text |Cite
|
Sign up to set email alerts
|

The CXC Chemokine Receptor 4 Ligands Ubiquitin and Stromal Cell-derived Factor-1α Function through Distinct Receptor Interactions

Abstract: Recently, we identified extracellular ubiquitin as an endogenous CXC chemokine receptor (CXCR) 4 agonist. However, the receptor selectivity and molecular basis of the CXCR4 agonist activity of ubiquitin are unknown, and functional consequences of CXCR4 activation with ubiquitin are poorly defined. Here, we provide evidence that ubiquitin and the cognate CXCR4 ligand stromal cell-derived factor (SDF)-1␣ do not share CXCR7 as a receptor. We further demonstrate that ubiquitin does not utilize the typical two-site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
127
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(141 citation statements)
references
References 69 publications
14
127
0
Order By: Relevance
“…This implies that CXCR4 and also ACKR3 function as modulators of α 1 -AR. Whereas the molecular mechanisms through which ACKR3 influences α 1 -AR function remain to be determined, the observed effects of ubiquitin in the present study are in agreement with the findings that ubiquitin functions as a noncognate CXCR4 agonist that does not bind to ACKR3 (51,52,(59)(60)(61)(62)(63). The observation that CXCL12, which has a much higher affinity for ACKR3 than for CXCR4 (64), also enhanced the potency of PE in normal animals in vivo in the present study, whereas CXCL12 previously desensitized PE-mediated vasoconstriction of isolated arteries and reduced blood pressure during hemorrhagic shock (9), suggests that effects of CXCL12 depend on the relative functional contribution of CXCR4 and ACKR3 within the specific experimental or (patho)physiological environment (65).…”
Section: Cxcr4 Agonists Increase the Potency Of Pe To Increase Bloodsupporting
confidence: 81%
See 2 more Smart Citations
“…This implies that CXCR4 and also ACKR3 function as modulators of α 1 -AR. Whereas the molecular mechanisms through which ACKR3 influences α 1 -AR function remain to be determined, the observed effects of ubiquitin in the present study are in agreement with the findings that ubiquitin functions as a noncognate CXCR4 agonist that does not bind to ACKR3 (51,52,(59)(60)(61)(62)(63). The observation that CXCL12, which has a much higher affinity for ACKR3 than for CXCR4 (64), also enhanced the potency of PE in normal animals in vivo in the present study, whereas CXCL12 previously desensitized PE-mediated vasoconstriction of isolated arteries and reduced blood pressure during hemorrhagic shock (9), suggests that effects of CXCL12 depend on the relative functional contribution of CXCR4 and ACKR3 within the specific experimental or (patho)physiological environment (65).…”
Section: Cxcr4 Agonists Increase the Potency Of Pe To Increase Bloodsupporting
confidence: 81%
“…5A shows a typical Western blot with anti-CXCR4 with cell homogenates from human VSMC transfected with nontargeting (NT) or CXCR4-targeted siRNA. As expected, anti-CXCR4 recognized multiple bands in human VSMC transfected with NT siRNA, which likely correspond to proteolytically processed, ubiquitylated, or glycosylated forms of CXCR4 (51)(52)(53)(54)(55). The most abundant receptor species after transfection of human VSMC with NT siRNA were detectable at migration positions corresponding to 48-60 kDa.…”
Section: Cxcr4 Silencing Inhibits α 1 -Ar Function In Vascular Smoothmentioning
confidence: 92%
See 1 more Smart Citation
“…Then, we investigated the inhibitory activity of CSB6B on the ubiquitin-protein interaction by examining the binding affinity of ubiquitin to CXCR4, a cell surface receptor that recognizes ubiquitin as a ligand [13][14][15]. Since ubiquitin binding to the cell surface would be mediated by CXCR4, the interaction of FITC-labeled ubiquitin with CXCR4 was assessed by measuring the fluorescence associated with human monocyte cells (THP-1) after treating CSB6B at various concentrations (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Recent progress in ubiquitin biology revealed that various forms of unanchored ubiquitin are also involved in cellular signaling [10][11][12]. For example, unanchored extracellular ubiquitin is responsible for apoptosis, cell growth, immune modulation, and cancer progression through its binding to CXC chemokine receptor type 4 (CXCR4) [13][14][15].…”
Section: Introductionmentioning
confidence: 99%